SYUBHAT DALAM PELAKSANAAN HUDUD MENURUT MUHAMMAD ABU ZAHRAH - Deden Najmudin; Januar Hukmawa Janatino; Meisa Sobariah; Ihsan Maulana; Imam Al Hafiz; Elsya Alfirani (Cahaya Ilmu Bangsa Institute, 2023)
Dalam hukum Islam,